Strategi Pokdarwis dalam Pengembangan Kampung Wisata Sanjai, Kota Bukittinggi - Hafifah, Nurul; Afrizal; Indraddin (UNIB Press, 2025)
This research explores how the Tourism Awareness Group (Pokdarwis) implementing Community-Based Tourism (CBT) in Sanjai Tourism Village, Bukittinggi, West Sumatera. By describing the strategies they have developed to promote tourism. As tourism serves as a vital economic driver, requires community involvement for sustainability. Employing a qualitative approach, this research gathers data through in-depth interviews, observations, and document analysis to assess Pokdarwis’ strategies in fostering tourism growth within the village. The analysis is framed using Bourdieu’s theoretical concepts of habitus, capital, and field. Key findings show Pokdarwis: (1) developing tourism plans; (2) promoting the destination; (3) utilizing social capital; (4) empowering pokdarwis members. Bourdieu’s concepts of habitus and capital (cultural, social, economic) highlight how shared norms and networks empower Pokdarwis to lead CBT sustainably. By blending local culture, strategic action, and community participation, Pokdarwis strengthens economic benefits while preserving cultural identity. This approach offers a model for policymakers and practitioners to enhance CBT through grassroots collaboration and socio-cultural alignment